Auricular acupoint pressing therapy and nursing of a patient with abdominal distension after ovarian cyst surgery by laparoscopy (耳穴压豆治疗1例卵巢囊肿患者腹腔镜术后腹胀的护理体会) - KONG Xiaochun (孔晓春); CAO Lei (曹蕾) (中西医结合护理)
This paper summarized the auricular acupoint pressing therapy and nursing of a patient with abdominal distension after ovarian cyst surgery by laparoscopy. Based on the Traditional Chinese Medicine syndrome differentiation, auricular acupoint pressing therapy and comprehensive nursing interventions including diet guidance and lifestyle care were carried out to relieve the abdominal distension after ovarian cyst surgery by laparoscopy. (本文总结采用耳穴压豆疗治疗1例卵巢囊肿患者腹腔镜术后腹胀的护理经验, 基于中医辨证施护理论指导, 辨证选取耳穴给予耳穴压豆, 并配合饮食指导、生活护理等常规护理, 有效缓解患者的腹胀症状。)